2022
DOI: 10.3390/ijms23010502
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Gamma Aminobutyric Acid against Aggravation of Renal Injury Caused by High Salt Intake in Cisplatin-Induced Nephrotoxicity

Abstract: Gamma-aminobutyric acid (GABA) is one of the inhibitory neurotransmitters. Several studies have suggested that GABA supplements can reduce blood pressure and modulate the renal immune system in vitro and in vivo. In the present study, we investigated the effect of GABA-enriched salt as an alternative to traditional salt on aggravated renal injury by high salt intake in cisplatin-induced nephrotoxicity mice. High salt intake accelerated the increase of biomarkers, such as blood urea nitrogen and serum creatinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The sodium chloride content of the parent seawater salt was not reported. The results are not very clearly expressed, but it appears that salt administration increased the severity of cisplatin-induced AKI as assessed by serum creatinine and urea, histological injury and expression of inflammatory mediators, while the different GABA-salt was protective, the results for lacto-GABA-salt and postbiotic-GABA-salt being unclear [90].…”
Section: Postbiotics In Nephrotoxic Akimentioning
confidence: 89%
See 1 more Smart Citation
“…The sodium chloride content of the parent seawater salt was not reported. The results are not very clearly expressed, but it appears that salt administration increased the severity of cisplatin-induced AKI as assessed by serum creatinine and urea, histological injury and expression of inflammatory mediators, while the different GABA-salt was protective, the results for lacto-GABA-salt and postbiotic-GABA-salt being unclear [90].…”
Section: Postbiotics In Nephrotoxic Akimentioning
confidence: 89%
“…Postbiotics have been studied in preclinical, but not in clinical AKI. In preclinical studies, AKI was induced by cisplatin administration to mice and the severity of injury was magnified by the oral administration of salt from 1 h prior to cisplatin up to 48 h post induction of AKI, with a 72 h readout [90]. GABA-salt was prepared as for the hypertension studies [87] with slight modifications involving further fermentation of Lactobacillus.…”
Section: Postbiotics In Nephrotoxic Akimentioning
confidence: 99%
“…Recent research suggests that postbiotics plays a significant role in preserving and improving kidney health in preclinical studies. Lee et al showed a beneficial effect of lacto-GABA-salt and postbiotics-GABA-salt (obtained from the fermentation of Lactobacillus plantarum BJ21 ) against cisplatin-induced renal histological changes [ 64 ]. Unfortunately, they do not provide details on the compounds obtained or the postbiotic composition.…”
Section: Discussionmentioning
confidence: 99%